2000
DOI: 10.1161/01.str.31.6.1230
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Knowledge Among Stroke Support Group Members

Abstract: Background and Purpose-Community stroke education is needed to improve early stroke recognition and reduce delays in the referral of stroke patients. In some regions, stroke support groups are important promoters of regional stroke education. However, there are no data about the level of stroke knowledge among support group members that support this promotional role. Methods-We performed a cross-sectional questionnaire survey among 11 German stroke support groups. The questionnaire asked for stroke knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 12 publications
4
50
1
2
Order By: Relevance
“…Eighty-seven per cent of the surveyed subjects were able to name at least two risk factors and, therefore, had good knowledge according to criteria set by Weltermann et al (15) (Figure 1B). This compares favourably with the number of people able to identify two or more risk factors (25% to 62%) in open-ended telephone surveys of the general population's knowledge of heart disease and stroke (7)(8)(9)).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Eighty-seven per cent of the surveyed subjects were able to name at least two risk factors and, therefore, had good knowledge according to criteria set by Weltermann et al (15) (Figure 1B). This compares favourably with the number of people able to identify two or more risk factors (25% to 62%) in open-ended telephone surveys of the general population's knowledge of heart disease and stroke (7)(8)(9)).…”
Section: Discussionmentioning
confidence: 94%
“…Alcohol abuse, hypertension, diabetes, age and sex were the five least commonly stated risk factors ( Figure 1A). Eightyseven per cent of subjects were able to name at least two risk factors and, therefore, had good knowledge according to criteria set by Weltermann et al (15). A total of 50% named at least four risk factors and had excellent knowledge.…”
Section: Risk Factor Awarenessmentioning
confidence: 93%
See 1 more Smart Citation
“…Weltermann and colleagues examined stroke awareness (stroke symptom knowledge) in 93 stroke patients and 40 family members and volunteers and found that history of prior stroke, age .70, and poor self-reported health status emerged as predictors of poor stroke knowledge. 15 While older age, 5,10 race, 5 and lower levels of education 5,10 are frequently associated with poor stroke awareness, sex (male), 5,10 hypertension, smoking status, and self-reported poor health status 10 have also been reported as independent factors associated with poor recognition of early warning signs of stroke. One significant predictor of greater stroke awareness did emerge: post-high school education.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of stroke awareness among individuals with stroke risk factors traditionally emphasize hypertension, 4,5,8,10 cardiovascular disease (CVD), 4,5,8,12 diabetes, 4,5,8,12 high cholesterol, 4,8,12,13 smoking history, 4,5,7,8,10,12 and other stroke risk factors. Fewer studies have considered individuals with prior history of stroke 14,15 even though estimates suggest that within five years, 24% of women and 42% of men with history of prior stroke will have a second stroke. 16 Further, individuals with history of prior stroke typically exhibit a number of associated factors (e.g., race/ethnicity, age, presence of other stroke risk factors) that increase their likelihood of a second stroke.…”
mentioning
confidence: 99%